(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
Based on the synthesis of hydrological, geological and hydrogeological data and reinterpretation of hydrogeophysical material we made a series of maps and specific incisions of regional aquitard of the Syunik Highland. In general, we have made paleo-hydrogeological zoning of the region that helped to clarify the distribution of the deep drain highlands; the maps of paleorelief are the basis for more detailed and focused prospecting and exploration of water.